The female reader and her relationship with the newspaper Estado de Minas (Perspectivas em Ciência da Informação, 2009)
The present paper looks into female reading and interaction in the newspaper Estado de Minas. It identifies the necessary elements to include women as newspaper readers as well as the way they report themselves and interact with those that "build up" and divulge the news. The study talks about information production through a male language, how women are included in that context and the possible impacts of journalistic information onto the female gender.